2021
DOI: 10.3389/fonc.2021.696422
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogression After Immunotherapy for Primary Small Cell Neuroendocrine Carcinoma of the Ureter: A Case Report

Abstract: BackgroundPrimary small cell neuroendocrine carcinoma (SCNEC) in the ureter is extremely rare and has been sporadically reported in case reports. Its incidence, diagnosis, treatment, and outcomes have not yet been thoroughly understood. Here we present a patient with advanced SCNEC in the ureter who was treated by multimodal strategies. To the best of our knowledge, this is the first literature report about the clinical outcomes of the combination of programmed death ligand 1 (PD-L1) immune checkpoint inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Primary ureteral SCNEC is commonly seen in elderly men and is presented with gross hematuria and lumbar pain ( 4 ). However, with no recommendation for extensive or advanced disease, PD-1/PD-L1 inhibitor remains the treatment for ureteral SCNEC ( 6 ). Immune-related adverse events are a range of complications associated with the use of immune-checkpoint inhibitors what cantinas PD-1/PD-L1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Primary ureteral SCNEC is commonly seen in elderly men and is presented with gross hematuria and lumbar pain ( 4 ). However, with no recommendation for extensive or advanced disease, PD-1/PD-L1 inhibitor remains the treatment for ureteral SCNEC ( 6 ). Immune-related adverse events are a range of complications associated with the use of immune-checkpoint inhibitors what cantinas PD-1/PD-L1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Small cell neuroendocrine carcinoma of the ureter is a highly malignant tumor originating from the metaplasia of urothelial cells with or without neuroendocrine function 1 . Due to its rare nature, ureteral SCNEC is always misdiagnosed or escapes diagnosis in the early stage and has a poor prognosis in the later stage on imaging 2 .…”
Section: Figurementioning
confidence: 99%
“…Small cell neuroendocrine carcinoma of the ureter is a highly malignant tumor originating from the metaplasia of urothelial cells with or without neuroendocrine function. 1 Due to its rare nature, ureteral SCNEC is always misdiagnosed or escapes diagnosis in the early stage and has a poor prognosis in the later stage on imaging. 2 However, SCNEC is usually detected by CT but rarely by ultrasonography and MRU, which could provide more features of ureteral SCNEC, including its composition, pattern, and blood flow.…”
mentioning
confidence: 99%
“…Primary ureteral NENs are rare, and no more than 50 cases of small-cell ureteral NEC have been reported in the literature [2,102]. Small-cell NEC of the ureter is usually observed in elderly patients, and around 15 cases have been observed in females so far [2,102,103]. As per our knowledge, less than 10 cases of large-cell NEC of the ureter [73,74] have been reported in the literature.…”
Section: Ureteral Nens 41 Epidemiology Presentation and Pathogenesismentioning
confidence: 99%
“…Endoscopy provides the biopsy specimen, which aids in diagnosing the mass by revealing malignant neuroendocrine cells [74,110]. A few may also present with paraneoplastic syndromes, which indicate advanced or extensive disease [102]. Ouzzane et al reported that 72% of patients presented with pT3 or pT4 stages, and 54% developed metastases within 13 months [108].…”
Section: Ureteral Nens 41 Epidemiology Presentation and Pathogenesismentioning
confidence: 99%